MANAGEMENT OF PRODUCTION FROM COMPLEX OIL FIELDS - Bekjonov Rozisher Soatmurodovich; Ismatov Sherzod Aktam ugli (American Journals Publishing, 2024)
However, when flooding fields with hard-to-recover reserves (high oil viscosity, low permeability and large heterogeneity of formations), oil recovery factors decrease to 0.3-0.35 with increasing flushing ratio from 0.8-1 to 5-7, and with viscosity oil more than 25-30 mPa s, waterflooding often becomes ineffective.Obviously, this method is characterized by a high degree of theoretical justification of the oil recovery mechanism and eliminates error due to the human factor due to the use of software and computing systems. This path, on the one hand, is very labor-intensive, and on the other hand, there is not always reliable information about the properties of productive formations.
Keywords: Oil, product, high oil viscosity, carbonate reservoirs, geologic model, waterflooding.